\[\boxed{\text{360\ (360).}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[1)\ 6x \cdot (6x - 4) + 9x \cdot (3 - 4x) =\]
\[= 36x^{2} - 24x + 27x - 36x^{2} =\]
\[= 3x.\]
\[при\ x = - \frac{1}{9}:\ \ \ \ \]
\[- 3 \cdot \frac{1}{9} = - \frac{1}{3}.\]
\[при\ m = - 4;\ n = 0,5:\]
\[2 \cdot 16 + 5 \cdot 4 \cdot 0,5 - 6 \cdot 0,5 =\]
\[= 32 + 10 - 3 = 39.\ \]
\[\boxed{\text{360.}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[1)\ 6x^{2} > 0\]
\[Неверно,\ так\ как\ при\ x^{2} = 0\ \]
\[выражение\ будет\ равно\ 0.\]
\[2)\ 0,4a^{4}b^{6} \geq 0\]
\[Верно,\ так\ как\ a^{4} \geq 0;\ \ b^{6} \geq 0\ \]
\[при\ любом\ значении.\]
\[3) - \frac{1}{3}a^{3} < 0\]
\[Неверно,\ так\ как\ при\ a \leq 0;\ \ \]
\[выражение\ будет \geq 0.\]
\[4) - 5b^{2} < 0\]
\[Неверно,\ так\ как\ при\ b = 0\ \]
\[выражение\ будет\ равно\ 0.\]